Microeconomic and Macroeconomic Factors Affecting Bank Credit Delinquency in Ecuador, period 2017-2022 - Guachamin Guerra, Marcela Elizabeth (2024)
Non-performing loans (NPL) in the Ecuadorian financial sector has increased in recent years. This study aims to identify the microeconomic and macroeconomic factors that influence the NLP rate of 23 private banks in Ecuador between 2017 and 2022, using the dynamic panel data GMM methodology. The contraction of demand and consumption during this period has revealed that a decrease in GDP leads to an increase in NLP. Similarly, it has been confirmed that an increase in inflation, unemployment, and the active interest rate also raises the NLP rate. At the microeconomic level, it was found that growth in the loan portfolio without considering the real payment capacity can increase NLP levels, and that a decrease in the ROA of the financial entity is reflected in an increase in the NLP rate. This study contributes to decision-making by supervisory entities and promotes the development of a strategic financial policy to minimize the impact of morosity on the Ecuadorian economy.